2001
DOI: 10.1046/j.0953-816x.2001.01769.x
|View full text |Cite
|
Sign up to set email alerts
|

mGlu1 receptors mediate a post‐tetanic depression at parallel fibre–Purkinje cell synapses in rat cerebellum

Abstract: Metabotropic glutamate (mGlu) receptors are located pre- and postsynaptically at central synapses. Activation of the receptors by exogenous agonists usually results in a reversible depression of fast glutamatergic neurotransmission. Evidence that synaptically released glutamate has such an action, however, is scarce. Sharp microelectrode recordings were used to investigate the modulatory role of mGlu receptors at a well-studied glutamatergic synapse, the one between parallel fibres and Purkinje cells in rat ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 51 publications
2
21
1
Order By: Relevance
“…Furthermore, we have characterized this phenomenon in terms of its dependence on the endocannabinoid system. Our work follows the path opened by several recent contributions, which established that the liberation of endocannabinoids by PLC-regulating pathways (both group I mGlu and M 1 /M 3 muscarinic receptors) can be an important mechanism leading to the depression of afferent synaptic inputs (Martin and Alger, 1999;Maejima et al, 2001;Neale et al, 2001;Varma et al, 2001;Robbe et al, 2002;Ohno-Shosaku et al, 2002a, 2003Chevaleyre and Castillo, 2003). Our experiments provide evidence that sustained activation of mGluR1s and CB1Rs triggers a transient modulation of the GABAergic synapses between basket-stellate cells and Purkinje cells.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, we have characterized this phenomenon in terms of its dependence on the endocannabinoid system. Our work follows the path opened by several recent contributions, which established that the liberation of endocannabinoids by PLC-regulating pathways (both group I mGlu and M 1 /M 3 muscarinic receptors) can be an important mechanism leading to the depression of afferent synaptic inputs (Martin and Alger, 1999;Maejima et al, 2001;Neale et al, 2001;Varma et al, 2001;Robbe et al, 2002;Ohno-Shosaku et al, 2002a, 2003Chevaleyre and Castillo, 2003). Our experiments provide evidence that sustained activation of mGluR1s and CB1Rs triggers a transient modulation of the GABAergic synapses between basket-stellate cells and Purkinje cells.…”
Section: Discussionmentioning
confidence: 95%
“…Activation of parallel fibers by extracellular stimulation has been shown previously to induce cannabinoid-mediated inhibition of glutamatergic synapses in Purkinje cells Neale et al, 2001;Brown et al, 2003). In contrast to Maejima et al (2001), who used strong stimulation protocols of the parallel fibers to obtain a weak inhibitory effect of the climbing fiber input, Brown et al (2003) reported that more physiological trains of action potentials limited the endocannabinoidmediated effect to the parallel fibers active during stimulation.…”
Section: The Heterosynaptic Inhibition Of Gabaergic Synaptic Inputs Bmentioning
confidence: 99%
See 1 more Smart Citation
“…A following study showed that activation of group I mGluR receptors, either by application of an exogenous agonist or by repetitive stimulation of parallel fibers, led to a retrograde inhibition of climbing fiber EPSPs , and that these effects were blocked by CB1R antagonists; hence these effects were proposed to be mediated by endocannabinoids. Likewise, brief repetitive stimulation of parallel fibres at high frequency leads to a transient self-inhibition: this was shown to depend on activation of mGluRs (Neale et al, 2001) and, following the development of endocannabinoid research, can now be ascribed to the synthesis and the action of endocannabinoids (Brown et al, 2003).…”
Section: The G-protein Coupled Receptor Pathway Of Retrograde Inhibitionmentioning
confidence: 99%
“…That mGluR activation is dependent on stimulus frequency/intensity has been observed in vitro in other brain areas where short bursts of high-frequency stimulation are necessary in order for the receptors to be activated by the synaptically released endogenous agonist (Scanziani et al 1997;Dube & Marshall, 2000;Mitchell & Silver, 2000;Semyanov & Kullmann, 2000;Neale et al 2001). We attempted to mimic patterns of visual responses with trains of stimuli applied at 20 and 50 Hz, in order to see if this could produce effects which were affected by the group II antagonist LY341495.…”
Section: Physiological Role For Group II Modulation Of Inhibitionmentioning
confidence: 99%